Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-27T16:57:53+01:00
A) 2x-7[5x²-3x-(2-4x+x²)]
2x-7[5x²-3x-2+4x-x²]
2x-35x²+21x+14-28x+7x²
-5x-28x²+14

b) 3-x²-[2-2x²-(3x²-2x+1)]
3-x²-[2-2x²-3x²+2x-1]
3-x²-2+2x²+3x²-2x+1
2+4x²-2x

c)4x+3-[x-3x²-(6-3x-x²)]
4x+3-[x-3x²-6+3x+x²]
4x+3-x+3x²+6-3x-x²
9+2x²

d)3x²-5x-[1-3x-(2+4x-x²)]
3x²-5x-[1-3x-2-4x+x²]
3x²-5x-1+3x+2+4x-x²
2x²+2x+1
1 5 1
2010-02-27T17:10:00+01:00
A) 2x-7[5x*2-3x-(2-4x+x*2)]=2x-7[5x*2-3x-2+4x-x*2]=
=2x-7[4x*2+x-2]=2x-28x*2-7x+14=-28x*2-5x+14
b)3-x*2-[2-2x*2-(3x*2-2x+1)]=3-x*2-[2-2x*2-3x*2+2x-1]=
=3-x*2-[-5x*2+2x+1]=3-x*2+5x*2-2x-1=4x*2-2x+2
c)4x+3-[x-3x*2-(6-3x-x*2)]=4x+3-[x-3x*2-6+3x+x*2]=
=4x+3-[-2x*2=4x-6]=4x+3+2x*2-4x+6=2x*2+9
d)3x*2-5x-[1-3x-(2+4x-x*2)]=3x*2-5x-[1-3x-2-4x+x*2]=
=3x*2-5x-[x*2-7x-1]=3x*2-5x-x*2+7x+1=2x*2+2x+1
1 5 1